Dimercaptosuccinic Acid Functionalized Polystyrene Column for Trace Concentration Determination of Heavy Metal Ions: Experimental and Theoretical Calculation Studies - Uzma Haseen (MDPI AG, 2021)
Metal ion studies in wastewater are required on a regular basis for environmental monitoring and assessment. Less metal ion concentrations and the interference from complex sample matrices remains challenging for instrumental quantification. Herein, we proposed a fix-bed solid phase extraction method, consisting of a newly prepared dimercaptosuccinic acid functionalized polystyrene beads. The ligand forms stable complex with Hg(II), Pb(II), and Cd(II), evident by experimental as well as density functional theory. The metal-ligand stabilization energy calculations, suggested the higher selectivity of polystyrene dimercaptosuccinic acid (PSDMSA) toward Pb(II) compared to Cd(II) and Hg(II). The prepared adsorbent was utilized to enrich Hg(II), Pb(II), and Cd(II) ions from environmental samples. Column parameters were studied in detail and optimized accordingly. The preconcentration factor for Hg(II), Pb(II), and Cd(II) were found to be 900, with the preconcentration limit of 0.74 µg L−1. The detection limit for Pb(II), Cd(II), and Hg(II) ions was found to be 1.3 ± 0.2, 1.5 ± 0.3, and 1.8 ± 0.3 ng L−1, respectively. The method accuracy was tested against systematic and continuous errors by standard addition method (<5% RSD). Real samples was successfully analyzed following the proposed method.